The Effect of Complementary Tu Ina Massage Therapy on Increasing Appetite in Toddlers at Posyandu Kampung Sukamulya II Ciseureuh Village as an Effort to Prevent Stunting - Darmayanti, Mey Linda (Jurnal Indonesia Sosial Sains, 2025)
Low appetite in toddlers is a common problem that can hinder growth and development. Complementary therapy from traditional Chinese medicine, particularly Tuina massage, is increasingly used and is believed to stimulate gastrointestinal function and improve appetite. This study aimed to determine the effect of Tuina massage on increasing toddlers’ appetite at Posyandu Kampung Sukamulya II, Ciseureuh Village. A quasi-experimental pretest–posttest two-group design was applied with total sampling (n=40): 20 toddlers in the intervention group and 20 in the control group. Caregiver-reported appetite was measured using a standardized scale; data were analyzed with paired and between-group tests at α = 0.05. In the intervention group, mean appetite scores improved from 2.90 at pre-test to 1.15 at post-test (p = 0.000), indicating better appetite (lower scores reflect improvement). The control group showed no change (pre-test 2.90; post-test 2.90; p = 1.000). The between-group comparison after the intervention was significant (p = 0.007), confirming the effect of Tuina massage on appetite. In conclusion, Tuina massage effectively improves toddlers’ appetite and can be considered a simple, safe, and low-cost adjunct within community nutrition programs. Implementation at the posyandu level should be accompanied by training for cadres and parents and integrated with feeding counseling; future controlled studies with larger samples and longer follow-up are recommended to strengthen generalizability.